Role of Polymer in the Catalysis of Acyl Transfer Reactions - BANGARU SUDARSAN ALWAR, S.; VIJAYA KUMAR, P.; KAMALI, T.V. (Asian Journal of Chemistry, 2010)
Preliminary study of kinetics of the hydrolysis of esters in the presence of polymer polyethyleneglycol (PEG) 6000 by hydroxide ion in varying solvent media has been carried out conductometrically. The results obtained throw light on the role of the catalysts in the mechanism of hedrolysis of esters. Further, the presence of polymer is found to modify the role of solvent during the course of the reaction. These preliminary results will pave way for predicting the nature of attack by enzymes on various substrates in biochemical reactions.